Human plasma‐derived immunoglobulin G fractionated by an aqueous two‐phase system, caprylic acid precipitation, and membrane chromatography has a high purity level and is free of detectable in vitro thrombogenic activity. Issue 2 (3rd December 2014) - Vargas, M.; Segura, Á.; Wu, Y.‐W.; Herrera, M.; Chou, M.‐L.; Villalta, M.; León, G.; Burnouf, T.
<x xml:space="preserve">Abstract</x> Background and Objectives Instituto Clodomiro Picado has developed an immunoglobulin G (IgG) plasma fractionation process combining a polyethylene glycol/phosphate aqueous two‐phase system (ATPS), caprylic acid precipitation and anion‐exchange membrane chromatography. We evaluated the purity and in vitro thrombogenicity of such IgG, in line with current international requirements. Materials and Methods Contributions of the different production steps to reduce thrombogenicity were assessed at 0·2 l‐scale, and then the methodology was scaled‐up to a 10 l‐scale and final products (n = 3) were analysed. Purity, immunoglobulin composition, and subclass distribution were determined by electrophoretic and immunochemical methods. The in vitro thrombogenic potential was determined by a thrombin generation assay (TGA) using a Technothrombin fluorogenic substrate. Prekallikrein activator (PKA), plasmin, factor Xa, thrombin and thrombin‐like activities were assessed using S‐2302, S‐2251, S‐2222, S‐2238 and S‐2288 chromogenic substrates, respectively, and FXI by an ELISA. Results The thrombogenicity markers were reduced mostly during the ATPS step and were found to segregate mostly into the discarded liquid upper phase. The caprylic acid precipitation eliminated the residual procoagulant activity. The IgG preparations made from the 10 l‐batches contained 100% gamma proteins, low residual IgA and undetectable IgM. The IgG subclass distribution was not substantially affected by the process. TGA and amidolytic activities revealed an undetectable in vitro thrombogenic risk and the absence of proteolytic enzymes in the final product. Conclusions Fractionating human plasma by an ATPS combined with caprylic acid and membrane chromatography resulted in an IgG preparation of high purity and free of a detectable in vitro thrombogenic risk.